The Connectivity Quality as Part of Network Quality For a Sparse Road Network - Hitapriya Suprayitno (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Institut Teknologi Sepuluh Nopember, 2018)
As a developing country, in terms of road network, Indonesia is dominated by sparse road network : the regency, the provincial and the national road network. Therefore, the network quality of the road network is capital to be formulated. This paper is designated to present the research result on formulating the connectivity quality as part of network quality. The network quality is formulated based on network performance to execute its function. The main functions are to connect different points of the region, to flow the traffic and to cover the area on a certain density. The connectivity quality must measure how well the nodes are connected each other. The quality must be measured against a desired condition. This principal is derived afterward into three measures, i.e. : the percentage of number of connected nodes, the percentage of the total road length and the ratio of total shortest path distance. Connectivity quality is calculated for each vehicle category. A special matrix method for transportation network analyses must be used to execute the whole calculation.